Temporal Resolution Enhancement in Compressed Video Sequences - Robertson Mark A (EURASIP Journal on Advances in Signal Processing, 2001)
Compressed video may possess a number of artifacts, both spatial and temporal. Spatial compression artifacts arise as a result of quantization of the transform-domain coefficients, and are often manifested as blocking and ringing artifacts. Temporal limitations in compressed video occur when the encoder, in an effort to reduce bandwidth, drops frames. Omitting frames decreases the reconstructed frame rate, which can cause motion to appear jerky and uneven. This paper discusses a method to increase the frame rate of video compressed with the DCT by inserting images between received frames of the sequence. The Bayesian formulation of the restoration prevents spatial compression artifacts in the received frames from propagating to the reconstructed frames.